Feasibility Analysis of Broiler Business with Partnership System (Case Study at Mr. Pujianto's Farm, Umbuldamar Village, Binangun District, Blitar Regency) - Arafat, Muhamad Irfan; Moelia, Edya (Universitas Veteran Bangun Nusantara, 2025)
This study aims to analyze the financial feasibility of broiler chicken farming under a partnership scheme between farmers and a core company in Umbuldamar Village, Blitar Regency. The research employed a case study approach using a descriptive quantitative method. Data collected included production costs, revenues, profits, and financial indicators such as Break Even Point (BEP), Revenue-Cost Ratio (R/C), and Payback Period (PP). The results indicate that broiler farming operated through a partnership model is financially feasible. The average R/C ratio was 1.10, BEP was 1,140 chickens, and the average payback period over three years was 3.03 years. The partnership scheme has proven effective in reducing business risks and ensuring product marketing for farmers. This study recommends the development of more equitable partnership models and increased production efficiency to enhance profitability